Effectiveness and safety of switching to entecavir hepatitis B patients developing kidney dysfunction during tenofovir. (7th January 2019) - Viganò, Mauro; Loglio, Alessandro; Labanca, Sara; Zaltron, Serena; Castelli, Francesco; Andreone, Pietro; Messina, Vincenzo; Ganga, Roberto; Coppola, Nicola; Marrone, Aldo; Russello, Maurizio; Marzano, Alfredo; et al.
Abstract: Background and Aims: Tenofovir disoproxil fumarate (TDF) is recommended for chronic hepatitis B (CHB) treatment, but it may induce kidney dysfunction whose management is not yet known. This Italian, multicentre, retrospective study aimed to assess the efficacy and safety of switching to entecavir (ETV) patients who developed TDF‐associated glomerular and/or tubular dysfunction. Methods: A total of 103 TDF‐treated patients were included as follows: age 64 years, 83% male, 49% cirrhotics, 98% with undetectable HBV DNA, 47% with previous lamivudine resistance (LMV‐R) and 71% previously treated with adefovir. Twenty‐nine (28%) were switched to ETV because estimated glomerular filtration rate (eGFRMDRD ) was <60 mL/min, 37 (36%) because blood phosphate (P) levels were <2.5 mg/dL and 37 (36%) for both reasons. Kidney, liver and virological parameters were recorded every 4 months thereafter. Results: During 46 (4‐115) months of ETV treatment, all patients' renal parameters significantly improved as follows: creatinine from 1.30 to 1.10 mg/dL ( P  < 0.0001), eGFRMDRD from 54 to 65 mL/min ( P  = 0.002), P from 2.2 to 2.6 mg/dL ( P  < 0.0001) and maximal tubule phosphate reabsorption (TmPO4/eGFR) from 0.47 to 0.62 mmol/L ( P  < 0.0001). Thirteen patients (52%) improved their eGFRMDRD class, P levels were normalised in 13 (35%), and eight (22%) showed improvements in both parameters. Viral suppression was maintained in all but five patients (5%), all of whom had been LMV‐R. The 5‐year cumulative probability of ETV‐R was 0% in LMV‐naïve patients, and 11% in LMV‐R patients ( P  = 0.018). Conclusions: Entecavir is an effective and safe rescue strategy for CHB patients who develop renal dysfunction during long‐term TDF treatment.